Herb-Drug Interaction Between Xiyanping Injection and Lopinavir/Ritonavir, Two Agents Used in COVID-19 Pharmacotherapy - Ye, Linhu; Cheng, Lei; Deng, Yan; Liu, Hong; Wu, Xinyu; Wang, Tingting; Chang, Qi; Zhang, Yan; Wang, Dan; Li, Zongze; Yang, Xixiao (Frontiers in Pharmacology, 2021)
The global epidemic outbreak of the coronavirus disease 2019 (COVID-19), which exhibits high infectivity, resulted in thousands of deaths due to the lack of specific drugs. Certain traditional Chinese medicines (TCMs), such as Xiyanping injection (XYPI), have exhibited remarkable benefits against COVID-19. Although TCM combined with Western medicine is considered an effective approach for the treatment of COVID-19, the combination may result in potential herb-drug interactions in the clinical setting. The present study aims to verify the effect of XYPI on the oral pharmacokinetics of lopinavir (LPV)/ritonavir (RTV) using an in vivo rat model and in vitro incubation model of human liver microsomes. After being pretreated with an intravenous dose of XYPI (52.5 mg/kg) for one day and for seven consecutive days, the rats received an oral dose of LPV/RTV (42:10.5 mg/kg). Except for the t1/2 of LPV is significantly prolonged from 4.66 to 7.18 h (p < 0.05) after seven consecutive days pretreatment, the pretreatment resulted in only a slight change in the other pharmacokinetic parameters of LPV. However, the pharmacokinetic parameters of RTV were significantly changed after pretreatment with XYPI, particularly in treatment for seven consecutive days, the AUC0-∞ of RTV was significantly shifted from 0.69 to 2.72 h μg/mL (p < 0.05) and the CL exhibited a tendency to decrease from 2.71 L/h to 0.94 L/h (p < 0.05), and the t1/2 of RTV prolonged from 3.70 to 5.51 h (p < 0.05), in comparison with the corresponding parameters in untreated rats. After administration of XYPI, the expression of Cyp3a1 protein was no significant changed in rats. The in vitro incubation study showed XYPI noncompetitively inhibited human CYP3A4 with an apparent Ki value of 0.54 mg/ml in a time-dependent manner. Our study demonstrated that XYPI affects the pharmacokinetics of LPV/RTV by inhibiting CYP3A4 activity. On the basis of this data, patients and clinicians can take precautions to avoid potential drug-interaction risks in COVID-19 treatment.